2017
DOI: 10.1007/s00330-017-5004-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer detection among readers with different degree of experience using ultra-high b-value diffusion-weighted Imaging: Is a non-contrast protocol sufficient to detect significant cancer?

Abstract: • Significant prostate cancer using zoomed ultra-high b-value DWI was detected. • Diagnostic performance among readers with different degrees of experience was good. • mp- MRI of the prostate using a comprehensive non-contrast protocol is clinically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…An initial 3502 studies underwent title and abstract screening, of which 127 studies were retrieved for full‐text review. In all, 31 studies reporting on 9480 patients (4296 with prostate cancer) met the inclusion criteria for meta‐analysis; 25 studies reported on mpMRI DTA (7000 patients, 2954 with prostate cancer), 12 studies reported on bpMRI DTA (2716 patients, 1477 with prostate cancer), and six studies directly compared mpMRI and bpMRI (2047 patients, 1063 with prostate cancer). Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial 3502 studies underwent title and abstract screening, of which 127 studies were retrieved for full‐text review. In all, 31 studies reporting on 9480 patients (4296 with prostate cancer) met the inclusion criteria for meta‐analysis; 25 studies reported on mpMRI DTA (7000 patients, 2954 with prostate cancer), 12 studies reported on bpMRI DTA (2716 patients, 1477 with prostate cancer), and six studies directly compared mpMRI and bpMRI (2047 patients, 1063 with prostate cancer). Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63].…”
Section: Resultsmentioning
confidence: 99%
“…Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63]. Seven studies were at high risk of bias , four were at low risk of bias , and the remaining 18 studies had an unclear risk of bias due to at least one of the four domains .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Widespread use of prostate MRI in men with clinical suspicion of PCa can create a major financial burned on healthcare systems around the world. Thus, the use of a more rapid and cost‐effective prostate MRI protocol without the use intravenous contrast agent is desired …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acquisition of a b = 2000 mm 2 /s may be a problem when calculating the ADC, since image noise at higher measured b‐values can lead to a calculation of falsely low ADC values, and therefore overestimation of the GS. On the other hand, numerous studies demonstrate the additional value of using high b‐values (>1500 s/mm 2 ) for the detection of sPCa . From the low b‐values that can be used for ADC calculation, however, high b‐values to increase sPCa detection can be extrapolated mathematically using different calculation models without additional measurement time, which could contribute to a more time‐ and cost‐effective protocol than that of the presented study.…”
mentioning
confidence: 86%